Do early prednisolone and other immunosuppressant therapies prevent generalization in ocular myasthenia gravis in Western populations: a systematic review and meta-analysis. (September 2019) - Li, Mingxia; Ge, Fangfang; Guo, Rongjing; Ruan, Zhe; Gao, Yanwu; niu, Chunxiao; Lin, Hong; Zhao, Zhengwei; Zhou, Yongan; Li, Zhuyi; Chang, Ting
Background: The majority of ocular myasthenia gravis (OMG) patients will progress to generalized myasthenia gravis (GMG), usually within 2 years of disease onset. The aim of this meta-analysis was to evaluate the effect of early prednisolone and other immunosuppressants therapy on the generalization rate in OMG patients. Methods: We searched the CENTRAL, EMBASE, and MEDLINE databases via the Ovid SP database for all relevant publications on 16 July 2018. Results: Eight studies comprising a total of 547 participants were included in our meta-analysis. Compared with pyridostigmine treatment, prednisolone and other immunosuppressants therapy produced an odds ratio (OR) for the development of GMG of 0.19 [95% confidence interval (CI), 0.11–0.30; I 2  = 37%], indicating that early prednisolone and other immunosuppressants therapy reduced the generalization rate in OMG by 81%. Conclusions: Early prednisolone and other immunosuppressants therapy can significantly reduce the risk of generalization in OMG patients, and should be considered in newly diagnosed OMG patients. Due to the inclusion of retrospective studies, this noted effect might have been related to corticosteroids, especially when immunosuppressants used at low dosages and in mild disease. Additionally, the data derived from Western populations, thus a prospective randomized controlled trial (RCT) is warranted to confirm this effect of early prednisolone and other immunosuppressants therapy on OMG generalization both in Western and Asian populations.